Physicochemical Properties of Green Tea Ice Cream Using Whipped cream and Beneng Taro Flour Substitution (Xanthosoma Undipes K.Koch) - Satar, Ibdal; Ratna Timur, Farradila Caesar (Universitas Brawijaya, 2026)
The integration of Beneng taro (TB) flour and green tea (TH) powder into ice cream represents a promising approach to developing functional food products. TB flour has a high starch and relatively low fat, making it a potential thickening and stabilizing agent, as well as a fat replacer, for substituting whipped cream (Wh-C). Meanwhile, TH powder is rich in polyphenols, contributing antioxidant properties that may enhance the functional value of the product. This study aimed to evaluate the effect of substituting Wh-C with TB flour on the physicochemical properties of ice cream. The experiment was conducted using a one-factor Completely Randomized Design (CRD) with five formulation ratios of Wh-C and TB flour: F0 (100:0), F1 (75:25), F2 (50:50), F3 (25:75), and F4 (0:100). Physicochemical parameters analyzed included overrun, melting time, moisture content, fat content, protein content, carbohydrate content, ash content, and antioxidant activity (IC50). Data were statistically analyzed using one-way ANOVA with SPSS version 23. The results showed that the physicochemical properties of ice cream were within the following ranges: overrun (11.83–58.59%), melting time (26.61–54.88 minutes), moisture (51.16–72.15%), ash (1.33–1.51%), fat (3.35–14.75%), protein (3.48–4.27%), carbohydrate (8.29–39.72%), and antioxidant activity (IC50: 102.19–110.42 ppm). The TB flour can be utilized as a potential fat replacer and functional ingredient in ice cream formulation, while TH powder enhances its antioxidant properties. The combination of both ingredients contributes to the development of a healthier ice cream product with improved functional value